Portrait of Islamic Leadership Contribution Towards Performance Success of Efforts to Improve Employee Quality - Azizah, Alissa Nur (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
Performance according to Islam is a form or way for individuals to actualize themselves. Performance is a real form of values, beliefs, and understanding that are embraced and based on strong moral principles and can be a motivation to produce quality work. Leadership has an important role in improving employee performance in a company. As is the case with the Islamic leadership style that has existed since the time of the Prophet with the four known characteristics, namely Shidiq, Amanah, Fatonah, and Tabligh. Testing the direct and indirect influence of Islamic leadership traits on employee performance is the aim of this research, by using employee involvement as a mediating variable. Explanatory research with primary data at the Tritya Eye Clinic was collected through an online Google Form questionnaire. The research results show that the nature of Islamic leadership has a direct influence on employee performance. Employee involvement is only able to mediate the nature of Islamic leadership (shindig) on employee performance.